PWE-051 Small Bowel Adenocarcinoma: Single Centre Experience Over 6 Years. (17th August 2016) - Moroni, F; Murray, G; Bain, G
Abstract : Introduction: Small bowel (SB) cancer is a rare condition (<5% of all gastrointestinal cancers). Small bowel adenocarcinoma (SBA) accounts for 40% of SB cancers. Incidence is rising, with an estimated 3600 cases per year in Europe, led by an increasing number of sporadic duodenal cases. 1, 2 Besides known predisposing conditions (i.e. Coeliac, Crohn's and familial diseases), alcohol consumption and smoking have been identified as environmental risk factors for SBA. 3 We reviewed cases of SBA in Aberdeen Royal Infirmary from 2010 to 2015 and compared with the available literature. Methods: We obtained all histology confirming SBA over the past 6 years from our Pathology Department. Patient case notes and electronic records were reviewed and relevant data as per literature review collected. Results: 28 cases of SBA were confirmed during 6 years: 17 male and 11 female (1.5:1 ratio). Mean age at diagnosis was 65 (46–82).19 cases (68%) from duodenum, 8 (28%) jejunum and 1 ileum. Majority were sporadic (22, 79%), 3 had Crohn's Disease, 2 genetic conditions (FAP and HNPCC) and 1 Coeliac disease.16 cases were diagnosed via radiology (57%), 10 (36%) via endoscopy and 2 incidentally at surgery. The commonest presentation was bowel obstruction (11, 39%), followed by melaena (6, 21%) and jaundice (3, 11%). Disease was advanced at time of diagnosis: 19 (68%) had at least T4N1 disease or metastasis. 17 patients (61%) died during this period with 76% mortality at 1 year. Average survival was 216 days.We found positive correlation between alcohol consumption and both staging and mortality in sporadic cancers (Pearson 0.8). The 3 youngest patients had Crohn's disease for >15 years with small bowel involvement, 2 had previous surgery and had been on Azathioprine for over 10 years, in 1 case this was discontinued for 12 years at time of cancer diagnosis. 1 Coeliac disease patient was diagnosed in his 7 th decade and developed duodenal cancer 6 years later. Conclusion: Our population findings are comparable to current literature. We confirm a high number of sporadic duodenal adenocarcinomas. Late presentation with bowel obstruction and an advanced stage of disease results in a high mortality, We demonstrated correlation between alcohol consumption and both mortality and disease severity. Smoking did not appear to be an environmental risk factor in our population. This may be due to our small sample size. Multi-centre collaboration would allow formation of larger registries and facilitate research in this area. References: 1 Shenoy S, et al. J Gastrointest Cancer . 2014 Dec;45 (4):421–30. 2 Chow JS, et al. International Journal of Epidemiology 1996;25 :722–8. 3 M. Bennett, et al. Cancer Epidemiol 2015 Jun;39 (3):265–73. Disclosure of Interest: None Declared